Deskripsi Kreativitas Siswa dalam Menyelesaikan Soal TIMSS - Ruslan; Hamda; Rahayu, Nur (Al Asma: Journal of Islamic Education, 2023)
This research explores students' creativity in solving problems using the TIMSS cognitive domain. This qualitative study employs a descriptive method with two eighth-grade students in Gowa as the research subjects. The selection of subjects is based on their initial mathematical abilities in the eighth grade, and students with high capabilities are grouped accordingly. The instruments used for data collection include a mathematics creativity test and interview guidelines. The study focuses on three aspects of creative thinking abilities: fluency, flexibility, and originality. The result of this study indicates that (1) the subject in the cognitive domain of applying algebraic content, high initial abilities meet the aspects of fluency and flexibility. This meant that obtained creative thinking ability level 3 (creative); (2) in the cognitive domain of reasoning, the subject's algebraic content fulfills the flexibility aspect. This means obtaining creative thinking ability level 2 (creative enough).